2006
DOI: 10.1111/j.1471-4159.2006.04393.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress activates protein tyrosine kinase and matrix metalloproteinases leading to blood–brain barrier dysfunction

Abstract: The blood-brain barrier (BBB) formed by brain microvascular endothelial cells (BMVEC) regulates the passage of molecules and leukocytes in and out of the brain. Oxidative stress is a major underlying cause of neurodegenerative and neuroinflammatory disorders and BBB injury associated with them. Using human BMVEC grown on porous membranes covered with basement membrane (BM) matrix (BBB models), we demonstrated that reactive oxygen species (ROS) augmented permeability and monocyte migration across BBB. ROS activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
199
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(214 citation statements)
references
References 64 publications
14
199
0
1
Order By: Relevance
“…37 Moreover, it has been demonstrated that oxidative stress can activate MMP-2 and MMP-9 via tyrosine kinase-dependent mechanisms, leading to BBB breakdown. 38 Proinflammatory cytokines are also suggested to induce the release of MMP-9 from brain pericytes in the damaged BBB. 39 Therefore, in T2DM, the accumulation of oxidative stress and inflammation response induce and activate MMPs, which further downregulate TJ proteins and promote swollen astrocytic end-feet, and ultimately lead to BBB dysfunction and subsequent cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, it has been demonstrated that oxidative stress can activate MMP-2 and MMP-9 via tyrosine kinase-dependent mechanisms, leading to BBB breakdown. 38 Proinflammatory cytokines are also suggested to induce the release of MMP-9 from brain pericytes in the damaged BBB. 39 Therefore, in T2DM, the accumulation of oxidative stress and inflammation response induce and activate MMPs, which further downregulate TJ proteins and promote swollen astrocytic end-feet, and ultimately lead to BBB dysfunction and subsequent cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors contributing to BBB disruption in ischemia, including generation of oxygen radicals (24,56,58), nitric oxide (22,42), production of vascular endothelial growth factor (67,69), and changes in intracellular calcium (5,26,35). Under normal conditions, the integrity of the BBB is maintained by tight junction complexes between adjacent brain capillary endothelial cells (2).…”
mentioning
confidence: 99%
“…In regard to the above, emerging evidence suggests that disruption of the BBB integrity, which can occur not only during SAE, but also during the course of various inflammatory disorders, may be the consequence of endothelial cell damage elicited by circulating bacterial LPS (17,37), proinflammatory cytokines, such as TNF-␣ (1, 39), high levels of ROS (e.g., H 2 0 2 ; Refs. 23,44), and/or NO produced by iNOS (37). In addition, it has been shown that exposure of cultured cerebrovascular endothelial cells to hypoxic insult (31) or serum obtained from multiple sclerosis (MS) patients reduce the expression of tight junctionassociated protein, occludin, and adherence junction protein, VE-cadherin, two major components of the intercellular junctions in the brain microvasculature that help to create and maintain the BBB (40,44).…”
Section: Discussionmentioning
confidence: 99%